Human Resource Reform and Transformational Leadership As a Determinant of Employee Professionalism: Analysis of the Role of Resistance Towards Change in Public Organizations - Elisabeth Ika Retno Widiani; Ima Kurnia Damayanti (Proceeding of The International Conference on Business and Economics, 2026)
This paper aims to analyze the influence of Human Resource Reform and Transformational Leadership on Civil Servant Professionalism, with Resistance to Change as a mediating variable. The research focuses on civil servants at the Semarang City Personnel, Education and Training Agency (BKPP Semarang City), an institution at the forefront of bureaucratic reform and talent management. A quantitative approach was employed through a survey of 77 civil servants using a saturated sampling technique. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the direct and mediation relationships between the research variables. The results showed that Human Resources Reform of Civil Servants and Transformational Leadership had a positive and significant effect on ASN Professionalism. Transformational Leadership was also proven to reduce Resistance to Change, while Human Resources Reform had an indirect effect through reducing resistance. In addition, Resistance to Change had a significant negative effect on ASN Professionalism and mediated the relationship between Human Resources Reform of Civil Servants and ASN Professionalism. These findings confirm that merit system reform, competency development, and inspirational leadership are key factors in improving ASN professionalism, especially when psychological and structural barriers in the form of resistance to change can be minimized. This study provides theoretical contributions in the development of a model of ASN professionalism as well as practical recommendations for local governments in strengthening the implementation of bureaucratic reform.